Teachers’ Views on Support by Environmental Non-Governmental Organisations in Selected Alexandra Township Primary Schools - Mawela, Ailwei Solomon (Koers, 2020)
This article explores teachers’ views regarding the support by environmental non-governmental organizations in managing environmental education (EE) projects in primary schools. In this qualitative case study research, a purposive sampling approach was used to sample thirteen (n=13) teachers from thirteen primary schools. Data was collected by means of using semistructured interviews and findings were analysed and discussed. The study was grounded in the total quality management theory and the interpretive paradigm, as it was concerned with the management of environmental education projects in primary schools. In order to examine how the environmental NGOs and, teachers’ management of environmental education projects in schools, the researcher drew on the concept of opportunity to learn (OTL). Findings indicated that teachers viewed environment NGOs as valuable in sharing the knowledge, skills, and experience in managing EE projects. Lack of time and resources were identified as additional barriers towards managing environmental projects in primary schools. Teachers were not trained as environmental educators, and they viewed managing EE projects in schools as additional work. Therefore, despite the efforts made by environmental NGOs managing school EE projects, the sustainability of these projects after NGOs disengagement was a problem in most schools. The article concludes with suggestions based on the findings, outlining how environmental NGOs can impart knowledge and skills in managing EE projects towards awareness of and involvement in the fight against pollution and the desecration of natural resources. https://doi.org/10.19108/KOERS.85.1.2383